The Effect of Dietary Protein Hydrolysate from Black Soldier Fly Larvae and Schizochytrium on Palatability, Nutrient Metabolites and Health Status in Beagle Dogs - Yu Wei; Lingfeng Xue; Deying Ma; Yuxiao Weng; Mingkang Liu; Luyang Li; Ziyi Dai; Ziyun Zhao; Haifeng Wang; Xiao Xu (Metabolites, 2024)
Protein hydrolysate from black soldier fly larvae (BSFP) has garnered great attention with its lower allergenicity, high amount of essential amino acids, and small bioactive peptides. Schizochytrium is a promising alternative source of n-3 FUFA because it has enriched docosahexaenoic acid (DHA, C22: 6). The aim of this study was to assess palatability, the presence of diarrhea, plasma biochemistry panels, anti-oxidative and anti-inflammatory effects, and immune function in beagle dogs when supplementing a mixture of protein hydrolysate from black soldier fly larvae and schizochytrium (BSFPs) into their diets. Experiment I: 24 young beagle dogs (16 males and 8 females; 4–5 months; BW: 6.40 ± 0.15 kg) were randomly divided into four groups: (1) control (CON), (2) 5% BSFPs, (3) 10% BSFPs, (4) 15% BSFPs. Their body weights and fecal scores were recorded, and blood samples were collected for analysis. Experiment II: three diets containing 5%, 10%, and 15% BSFPs were evaluated by comparing them with a basal diet (CON) to evaluate palatability. These results suggested that a lower presence of diarrhea existed in the BSFP diet than the CON diet (p < 0.05). Three treatment groups remarkably increased their total protein (TP) and albumin (ALB) contents and decreased their concentrations of triglyceride (TG) and total cholesterol (TC) in plasma (p < 0.05). Moreover, the 5% and 15% BSFPs groups had a higher calcium (CA) content in plasma, and the activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) and contents of creatinine (CREA) and urea nitrogen (BUN) were significantly reduced by supplementing BSFP in their diets (p < 0.05). Their anti-oxidative enzyme activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) were dramatically enhanced, and their malondialdehyde (MDA) concentrations were remarkably reduced (p < 0.05). Immunoglobulin A and G (IgA and IgG) concentrations in the plasma in the 10% and 15% BSFPs groups were significantly increased (p < 0.05). Furthermore, lower interleukin-8 (IL-8) contents were shown in the BSFP diets than the CON diet (p < 0.05). Similarly, the diets supplemented with BSFPs exhibited a positive effect on palatability (p < 0.05). To sum up, the diets supplemented with BSFPs significantly enhanced palatability, immune function, and anti-oxidative and anti-inflammatory capacity to alleviate diarrhea and improve the general health of the beagle dogs.